2022
DOI: 10.3390/ijms232315038
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Antibiotics and Nanomaterial Combinations as Therapeutic Strategies in the Management of Multidrug-Resistant Infections: A Review

Abstract: Antibiotic resistance has become a major public health concern around the world. This is exacerbated by the non-discovery of novel drugs, the development of resistance mechanisms in most of the clinical isolates of bacteria, as well as recurring infections, hindering disease treatment efficacy. In vitro data has shown that antibiotic combinations can be effective when microorganisms are resistant to individual drugs. Recently, advances in the direction of combination therapy for the treatment of multidrug-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 188 publications
(256 reference statements)
0
13
0
Order By: Relevance
“…Since metal NPs do not aim to induce alterations in metabolic pathways, they cannot trigger the bacterial resistance mechanisms, so these agents can be considered excellent candidates for the treatment of UTIs. Still, the production process of these instruments may have detrimental effects on the environment and raise questions with regard to the side effects manifested in the patients [ 36 , 131 , 157 , 158 ]. To overcome these concerns, M. Abd Elkodous et al [ 159 ] studied zinc oxide nanoparticles (ZnO NPs) produced in an eco-friendly and cost-effective manner through the sol-gel method [ 159 ].…”
Section: Nanotechnology Used As a Diagnostic Methods And In Antimicro...mentioning
confidence: 99%
“…Since metal NPs do not aim to induce alterations in metabolic pathways, they cannot trigger the bacterial resistance mechanisms, so these agents can be considered excellent candidates for the treatment of UTIs. Still, the production process of these instruments may have detrimental effects on the environment and raise questions with regard to the side effects manifested in the patients [ 36 , 131 , 157 , 158 ]. To overcome these concerns, M. Abd Elkodous et al [ 159 ] studied zinc oxide nanoparticles (ZnO NPs) produced in an eco-friendly and cost-effective manner through the sol-gel method [ 159 ].…”
Section: Nanotechnology Used As a Diagnostic Methods And In Antimicro...mentioning
confidence: 99%
“…Nevertheless, the formulation of a novel drug cannot be designed immediately with the mutation of bacteria, and antibiotics at higher doses may be associated with toxicity problems beyond the tolerance level. Moreover, these protocols will increase antibiotic misuse and the possibility of multidrug-resistant strains [ 58 ]. On the other hand, when NPs are conjugated or coated with other compounds, their activities are considerably improved.…”
Section: Antimicrobial Activity and Mechanisms Of Metallic Nanoparticlesmentioning
confidence: 99%
“…The antibacterial test showed particles at higher concentrations exhibited better antibacterial performance [ 96 ]. Hedaiat et al synthesized similar NPs using the Taguchi method and found that these NPs can be used in the manufacturing of dental and medical devices with antibacterial efficacy due to their optimum antibacterial properties [ 58 ]. Further, Safaei et al prepared Co-oxide NPs (Co 3 O 4 NPs) using leaf extracts of populous ciliates [ 97 ].…”
Section: Recent Developments In Antimicrobial Agents Based On Metalli...mentioning
confidence: 99%
“…Still, their antibacterial effectiveness declines as bacteria become resistant. 3 Polyethylene terephthalate (PET) is a vital textile material owing to its simple manufacturing process and outstanding mechanical properties. 4,5 However, the lack of antibacterial properties in PET-based textiles restricts their growth and high-end use in the medical and healthcare fields.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are frequently used to treat bacterial illnesses. Still, their antibacterial effectiveness declines as bacteria become resistant 3 . Polyethylene terephthalate (PET) is a vital textile material owing to its simple manufacturing process and outstanding mechanical properties 4,5 .…”
Section: Introductionmentioning
confidence: 99%